Novel Cold-Adapted Esterase MHlip from an Antarctic Soil Metagenome - Berlemont, Renaud (2013)
An Antarctic soil metagenomic library was screened for lipolytic enzymes and allowed for the isolation of a new cytosolic esterase from the a/b hydrolase family 6, named MHlip. This enzyme is related to hypothetical genes coding esterases, aryl-esterases and peroxydases, among others. MHlip was produced, purified and its activity was determined. The substrate profile of MHlip reveals a high specificity for short p-nitrophenyl-esters. The apparent optimal activity of MHlip was measured for p-nitrophenyl-acetate, at 33 °C, in the pH range of 6?9. The MHlip thermal unfolding was investigated by spectrophotometric methods, highlighting a transition (Tm) at 50 °C. The biochemical characterization of this enzyme showed its adaptation to cold temperatures, even when it did not present evident signatures associated with cold-adapted proteins. Thus, MHlip adaptation to cold probably results from many discrete structural modifications, allowing the protein to remain active at low temperatures. Functional metagenomics is a powerful approach to isolate new enzymes with tailored biophysical properties (e.g., cold adaptation). In addition, beside the ever growing amount of sequenced DNA, the functional characterization of new catalysts derived from environment is still required, especially for poorly characterized protein families like α/b hydrolases